The Ulleungdo Dispute of 1693 and the Myth of Japan's Sovereignty over Dokdo - Jo, Kyu-hyun (WILAYAH: The International Journal of East Asian Studies, 2025)
I examine the Ulleungdo Dispute of 1693 to demonstrate that Ulleungdo and Dokdo were already confirmed to be Korean territories in 1693 and that Japan did not "discover" these islands and own them in the late 17th Century. The Dajokan Directive of 1877 later reconfirmed this fact. Collectively, the Ulleungdo Dispute and the Dajokan Directive not only show that Japan did not establish sovereignty over Dokdo in the late 17th century, but also clearly demonstrate that Korea had legitimately won the Ulleungdo Dispute and that the conclusion of the Dispute still retains its historicity and legality by remaining valid for over a century. Finally, this article clearly demonstrates that it was impossible for the Dajokan Directive to have confused the identity of Takeshima because it reaffirmed the conclusion drawn from the Ulleungdo Dispute of 1693 which confirmed Dokdo and Ulleungdo to be adjacent Korean territories.